A generalization of Banach’s contraction principle
A generalization of Banach’s contraction principle
Let <inline-formula content-type="math/mathml"> <mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" alttext="upper T colon upper M right-arrow upper M"> <mml:semantics> <mml:mrow> <mml:mi>T</mml:mi> <mml:mo>:</mml:mo> <mml:mi>M</mml:mi> <mml:mo stretchy="false">→<!-- → --></mml:mo> <mml:mi>M</mml:mi> </mml:mrow> <mml:annotation encoding="application/x-tex">T:M \to M</mml:annotation> </mml:semantics> </mml:math> </inline-formula> be a mapping of a metric space <inline-formula content-type="math/mathml"> <mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" alttext="left-parenthesis upper M comma d right-parenthesis"> <mml:semantics> <mml:mrow> …